Influence of external factors on the quality indicators of fabrics with porous polyurethane coating - Yulia I. Maruschak; Natallia N. Yasinskaya (Vestnik of Vitebsk State Technological University)
The quality of fabrics with a porous polyurethane coating is manifested through consumer properties, and therefore it is of practical interest to study the influence of various operating conditions (external factors) on these properties. The authors have developed and implemented a technology and also released pilot batches of fabrics with a porous polyurethane coating intended for the manufacture of second- and third-layer clothing. However, there is no information on the resistance of such materials to external influences, which justifies the relevance of the studies conducted in this work. The purpose of the work is to determine the influence of the most significant external factors (abrasion, the effect of low and high temperatures) on the quality indicators of fabrics with a porous polyurethane coating for clothing purposes. Conducting these studies is essential for ensuring the reliable operation of products. The results obtained will allow the confection of materials for clothing, taking into account the operating conditions of the product.